Enhanced passive safety surveillance of the MF59-adjuvanted quadrivalent influenza vaccine in the elderly during the 2021/22 influenza season. Issue 1 (31st December 2023) - Amicizia, Daniela; Domnich, Alexander; Lai, Piero Luigi; Orsi, Andrea; Icardi, Giancarlo; Tkach-Motulyak, Oksana; Panatto, Donatella
ABSTRACT: In accordance with European directives, each year the enhanced safety surveillance (ESS) of seasonal influenza vaccines should be conducted in order to detect any potential increase in reactogenicity when the vaccine composition is updated or a new formulation becomes available. The objective of this passive ESS (EPSS) was to assess the frequency of spontaneously reported adverse events (AEs) following vaccination with the 2021/22 formulation of the MF59-adjuvanted quadrivalent influenza vaccine (aQIV) among older adults in Italy through the collection of data within a short time period (start of seasonal influenza vaccination) in order to monitor the reactogenicity of aQIV early in the season. All AEs reported within seven days following vaccination were analyzed by type and seriousness. In all, 1, 059 vaccination cards were distributed to individuals aged ≥65 years. Only one, non-serious, spontaneous individual case safety report was submitted, yielding an overall rate of 0.9 per 1, 000 doses administered. This report consisted of a reactogenic AE of pyrexia. The EPSS confirmed that the reactogenicity profile of aQIV was consistent with the known safety profile of the previous trivalent formulation. These optimal safety data could bolster public confidence in influenza vaccination and help to improve vaccination coverage.